A dermoscopy case series of cutaneous metastases from breast cancer in Filipino females - Rouslia Q. Alfaro; Arunee H. Siripunvarapon; Maria F. S. Quinio; Celine M. H. Duran; Joanne R. Pamin; Claire M. R. Habito (Wiley, 2024)
Abstract There is a limited number of dermoscopic images of cutaneous metastases from breast cancer. We report three cases of cutaneous metastases in Filipino females with breast cancer. They were referred to the Dermatology outpatient clinic with round, firm, nontender, erythematous nodules on the chest and trunk. Dermoscopic findings noted were linear, irregular, arborizing and polymorphic vessels, bright white lines at the periphery and white areas, homogenous yellow to yellow‐orange structureless areas with linear fissure‐like structures and irregular diffuse blue‐black pigmentation, multiple brown dots and globules, and pink homogeneous areas. The clinical presentation, dermoscopy, histopathology and immunohistochemistry findings were consistent with cutaneous metastases from breast cancer. Familiarity and knowledge of dermoscopic patterns will improve diagnostic accuracy and early recognition of cutaneous metastases.